EDUKASI DAMPAK PENGGUNAAN GADGET PADA ANAK-ANAK DI DESA MEUNASAH KEUDE KECAMATAN MESJID RAYA KABUPATEN ACEH BESAR - Zahara, Hafni; Haikal, Muhammad; Utama, T. Juanda Putra (JOURNAL OF SUSTAINABLE COMMUNITY SERVICE, 2023)
The rapid evolution of technology has ushered in significant transformations across various facets of life, where gadgets have emerged as indispensable tools for individuals spanning all age groups, including parents, adults, and even the youngest members of society. However, akin to other technological innovations, gadgets bring with them a dual-edged sword, offering both advantages and disadvantages. Unrestricted and unsupervised gadget usage can potentially exert detrimental effects on the growth and development of children. The ubiquitous accessibility and enticing features often entrap many children in addictive cycles of gadget engagement. Failure to address this issue can cast a shadow on a child's holistic maturation and overall development. In this context, the role of parents assumes paramount importance as they navigate their children's interaction with gadgets. It is incumbent upon parents to adopt a vigilant stance, actively participating in, supervising, and delineating clear boundaries for gadget utilization. These strategies represent the arsenal available to parents as they undertake the vital task of educating their children and proactively combatting the specter of gadget addiction.